Herp depletion inhibits zearalenone-induced cell death in RAW 264.7 macrophages. (April 2016) - Chen, Fenglei; Lin, Pengfei; Wang, Nan; Yang, Diqi; Wen, Xin; Zhou, Dong; Wang, Aihua; Jin, Yaping
Abstract: Herp is an endoplasmic reticulum (ER) membrane protein and strongly induced by the ER stress that not only participates in the unfolded protein response (UPR) under the ER stress, but also in cell autophagy under glucose starvation (GS). However, we do not know whether Herp plays any roles in other responses, such as zearalenone (ZEA). In this study, we constructed recombinant lentiviral vectors for Herp shRNA expression and generated stable Herp knockdown RAW 264.7 macrophages. Flow cytometry analysis showed Herp depletion could inhibit cell death induced by ZEA. Western blot analysis revealed that Herp depletion could up-regulate autophagy-related protein LC3-I conversion into LC3-II and the expression of ER stress-related protein CHOP. These results suggest that Herp depletion inhibits cell death by up-regulating autophagy. Highlights: ZEA up-regulated ER stress-related proteins Herp expression and autophagy-related protein LC3-I conversion to LC3-II in dose- and time-dependent manners. Herp depletion up-regulated LC3-I conversion to LC3-II treated with ZEA. Herp depletion had a protective role in ZEA-induced cell death via up-regulating autophage.